Literasi Media Digital Staf Frontliner terhadap Kesiapan Penanganan Hoaks Kesehatan di RSUD Welas Asih Provinsi Jawa Barat - Muhamad Habibie; Hudi Santoso (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of digital media has increased the complexity of health information flows and triggered the spread of misinformation, thereby requiring service personnel to be prepared to manage information critically. However, studies specifically examining the relationship between digital media literacy and readiness to handle health hoaxes among non-medical frontliner staff remain limited. This study aims to analyze the relationship between digital media literacy and readiness in handling health-related hoaxes among frontliner staff at RSUD Welas Asih Bandung. A quantitative approach with a survey method was employed, involving 243 respondents selected through a census sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through validity, reliability, and Spearman’s Rank correlation tests. The results indicate that digital media literacy is at a high level, with digital safety (85.2%) and digital ethics (82.3%) as dominant indicators. Readiness in handling health hoaxes is also high, with gathering (78.6%) and planning (76.1%) as the highest indicators. The correlation test shows a positive and significant relationship with a coefficient of 0.794 (p<0.001), indicating a strong association. These findings suggest that improving digital media literacy significantly contributes to enhancing readiness in handling health hoaxes. Therefore, strengthening digital literacy is an important strategy to improve communication effectiveness and healthcare service quality.